Palaeomagnetic comparison of a new fit of East and West Gondwanaland with the Smith and Hallam fit - Embleton, B. J J; Veevers, J. J.; Johnson, B. D.; powell, C. Mc A (Tectonophysics, 1980)
Palaeomagnetic data for five time intervals in the Phanerozoic are compared for a new fit of East (Antarctica, Australia, India) and West (Africa, Madagascar, South America) Gondwanaland and the hitherto durable fit of Smith and Hallam. The dispersion of the Palaeomagnetic poles is marginally less on the Smith and Hallam fit for four time intervals and marginally greater for the remaining one (Permo-Triassic). The Permo-Triassic poles of East Gondwanaland are evenly distributed between India and Australia and the decreased dispersion of the poles for this period on the new fit of East and West Gondwanaland is paralleled by the decreased dispersion of the poles for both India and Australia. Within the limitations of the analysis imposed by the data, the palaeomagnetic comparison shows that there is little to choose between the two fits.